Neurocognitive changes in associative- and working memory with aging - Feeney, Joanne (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2010)
This thesis sought to determine the nature of associative- and working memory dechne during adulthood, and to try and elucidate some of the factors which contribute to this age- related mnemonic decline. In the first study we examined associative- and working memory decline in group of healthy individuals aged 18-64 years. We found that significant impairments in both associative memory and working memory function emerged in the 5th decade of life. Controlling for IQ and education, there remained a significant age-related deficit.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin